Causes and MEchanisms foR non-atopic Asthma in Children (CAMERA) study: rationale and protocol - Mary Njoroge; Gabriela Pimentel Pinheiro; Cinthia Vila Nova Santana; Hajar Ali; Stephanie Hobbs; Santiago Mena-Bucheli; Natalia Romero-Sandoval; Steven Robertson; Charlotte E. Rutter; Donna Davoren; Collin Brooks; Jeroen Douwes; et al. (Respiratory Research)
Abstract Background The Causes And MEchanisms foR non-atopic Asthma in children (CAMERA) study was designed to investigate risk factors and mechanisms of non-atopic asthma in children and young adults in Brazil, Ecuador, Uganda, and New Zealand. Initial epidemiological analyses using existing datasets identified and compared risk factors for both atopic and non-atopic asthma. The focus of this paper is the protocol for sample collection and analysis of clinical data on possible non-atopic mechanisms. Methods In each of the four centres, the CAMERA study will enroll 160 participants aged 10–28 years, equally distributed among atopic asthmatics (AA), non-atopic asthmatics (NAA), atopic non-asthmatics and non-atopic non-asthmatics. Participants will be new recruits or returning World ASthma Phenotypes (WASP) study participants. Phase I consists of skin prick tests to define atopy, a general CAMERA questionnaire that covers respiratory and general health to identify asthma cases, followed by an asthma control questionnaire for asthmatics only. Phase II consists of a stress questionnaire and the following clinical assessments: lung function, nasal cytology, blood sampling, in vitro whole blood stimulation to assess IFN-γ production, hair cortisol concentration, dry air and capsaicin challenges, plus in a subset, cold air challenges. Analyses will compare inflammatory, physiological and clinical parameters across the four groups overall and by country. Discussion Here, we present the protocol for the CAMERA study, to provide relevant methodological details for CAMERA publications and to allow other centres globally to conduct similar analyses. The findings of this mechanistic multi-centre study will inform new and phenotype-specific prevention and treatment approaches. Clinical trial number Not applicable.